Research on the relationship between gaze anxiety, social media disorder, and perceived discrimination in medical students - Yanan Zheng; Die Hu (Scientific Reports)
Abstract To explore the current situation of gaze anxiety and its relation with social media disorder and perceived discrimination in medical students, this study aimed to provide insights for the reform of medical communication education. A cross-sectional design was adopted, 811 medical students were selected, and they were investigated with the Chinese version of gaze anxiety rating scale, the Chinese short version of social media disorder scale and perceived discrimination questionnaire in May 2022. The results revealed that medical students’ gaze anxiety was the highest in the daily dimension, and there was a statistically significant difference among different grades (F = 13.063, p < 0.001); gaze anxiety was positively correlated with social media disorder (r = 0.504, p < 0.01) and perceived discrimination (r = 0.505, p < 0.01); social media disorder has a direct positive effect on medical students’ gaze anxiety and may also indirectly influence it through perceived discrimination. The conclusion was that perceived discrimination can play a partial mediating role between gaze anxiety and social media disorder among medical students.